Vitamin D3 preserves blood retinal barrier integrity in an in vitro model of diabetic retinopathy - Lazzara, Francesca; Longo, Anna Maria; Giurdanella, Giovanni; Lupo, Gabriella; Platania, Chiara Bianca Maria; Rossi, Settimio; Drago, Filippo; Anfuso, Carmelina Daniela; Bucolo, Claudio (Frontiers in Pharmacology, 2022)
The impairment of the blood retinal barrier (BRB) represents one of the main features of diabetic retinopathy, a secondary microvascular complication of diabetes. Hyperglycemia is a triggering factor of vascular cells damage in diabetic retinopathy. The aim of this study was to assess the effects of vitamin D3 on BRB protection, and to investigate its regulatory role on inflammatory pathways. We challenged human retinal endothelial cells with high glucose (HG) levels. We found that vitamin D3 attenuates cell damage elicited by HG, maintaining cell viability and reducing the expression of inflammatory cytokines such as IL-1β and ICAM-1. Furthermore, we showed that vitamin D3 preserved the BRB integrity as demonstrated by trans-endothelial electrical resistance, permeability assay, and cell junction morphology and quantification (ZO-1 and VE-cadherin). In conclusion this in vitro study provided new insights on the retinal protective role of vitamin D3, particularly as regard as the early phase of diabetic retinopathy, characterized by BRB breakdown and inflammation.